2019
DOI: 10.1007/s11119-019-09638-w
|View full text |Cite
|
Sign up to set email alerts
|

An economic feasibility assessment of autonomous field machinery in grain crop production

Abstract: A multi-faceted whole farm planning model is developed to compare conventional and autonomous machinery for grain crop production under various benefit, farm size, suitable field day risk aversion, and grain price scenarios. Results suggest that autonomous machinery can be an economically viable alternative to conventional manned machinery if the establishment of intelligent controls is cost effective. An increase in net returns of 24% over operating with conventional machinery is found when including both inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…Sørensen et al (2005), Pedersen et al (2006Pedersen et al ( ), (2008 and Pedersen et al (2017) focused on sugar beet. Sørensen et al (2005), Pedersen et al (2006), Gaus et al (2017) and Shockley and Dillon (2018) estimated some benefits for cereals. The focus on automation/robotics for horticulture is logical because it is often a high value crop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sørensen et al (2005), Pedersen et al (2006Pedersen et al ( ), (2008 and Pedersen et al (2017) focused on sugar beet. Sørensen et al (2005), Pedersen et al (2006), Gaus et al (2017) and Shockley and Dillon (2018) estimated some benefits for cereals. The focus on automation/robotics for horticulture is logical because it is often a high value crop.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reviewed focused on one or two crops, but two of the studies were whole farm (i.e. Sørensen et al 2005;Shockley and Dillon 2018).…”
Section: Characteristics Of the Full-text Studies Analysedmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial investment in row crop robotics systems may become very big for an average farmer [10]. As much as USD 319,864 for an 850 ha farm is required for investment in intelligent machines to achieve maximum break-even point [104]. Fortunately, [104,105] concluded that farming robots would bring profitable business to farmers because robots can reduce 20% of the scouting costs for cereals, 12% for sugar beet weeding, and 24% for inter-row weeding.…”
Section: Challenges In Commercial Deployment Of Agricultural Robotsmentioning
confidence: 99%
“…As much as USD 319,864 for an 850 ha farm is required for investment in intelligent machines to achieve maximum break-even point [104]. Fortunately, [104,105] concluded that farming robots would bring profitable business to farmers because robots can reduce 20% of the scouting costs for cereals, 12% for sugar beet weeding, and 24% for inter-row weeding. Robots can work like a swarm of small robots to accomplish farm operation at a very competitive cost compared to current machines [106].…”
Section: Challenges In Commercial Deployment Of Agricultural Robotsmentioning
confidence: 99%